1999
DOI: 10.1021/np990041c
|View full text |Cite
|
Sign up to set email alerts
|

Strong Antinociceptive Effect of Incarvillateine, a Novel Monoterpene Alkaloid from Incarvillea sinensis

Abstract: Incarvillea sinensis is a wild plant distributed in northern China. The dried whole plant has been traditionally used to treat rheumatism and relieve pain as an ancient Chinese crude drug. To investigate its antinociceptive activity, we evaluated several fractions derived from the methanolic extract of Incarvillea sinensis in the formalin-induced pain model in mice. Incarvillateine, a novel monoterpene alkaloid, has been found to show significant antinociceptive activity. Here we report the antinociceptive act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 11 publications
0
31
1
Order By: Relevance
“…After 1 h reaction, the reaction solution was concentrated under reduced pressure, and the residue was purified by column chromatography on silica gel with CHCl 3 Synthesis of 4,4-Dihydroxy-a a-truxillic Acid Dimethylester (4) To a solution of 4,4Ј-dihydroxy-a-truxillic acid (1.0 g, 3.05 mmol) in methyl ethyl ketone (40 ml) and MeOH (20 ml), trimethylsilyldiazomethane (4 ml) in ether (10 ml) was added dropwise under stirring. After 1 h reaction, the reaction solution was concentrated under reduced pressure, and the residue was purified by column chromatography on silica gel with hexane-AcOEt …”
Section: )mentioning
confidence: 99%
“…After 1 h reaction, the reaction solution was concentrated under reduced pressure, and the residue was purified by column chromatography on silica gel with CHCl 3 Synthesis of 4,4-Dihydroxy-a a-truxillic Acid Dimethylester (4) To a solution of 4,4Ј-dihydroxy-a-truxillic acid (1.0 g, 3.05 mmol) in methyl ethyl ketone (40 ml) and MeOH (20 ml), trimethylsilyldiazomethane (4 ml) in ether (10 ml) was added dropwise under stirring. After 1 h reaction, the reaction solution was concentrated under reduced pressure, and the residue was purified by column chromatography on silica gel with hexane-AcOEt …”
Section: )mentioning
confidence: 99%
“…Furthermore, it displayed a significant antinociceptive effect which was partially blocked by pretreatment of naloxone, the narcotic antagonist, in the early phase of the formalin test. 10) In the present study, we used the more selective opioid receptor antagonists nor-BNI, b-FNA and NTI in the formalin test. INCA-induced antinociception in both early and late phases was markedly reduced by s.c. pretreatment with b-FNA, a selective m-opioid receptor antagonist, and nor-BNI, a selective k-opioid receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested the possibility that the action of INCA was partially related to its influence on the central opioid pathways. 10) However, details on the pharmacological aspect of the mechanism have not, to our knowledge, been undertaken.…”
mentioning
confidence: 99%
“…98) This compound has been found to show potent analgesic activity in a formalin-induced pain model in mice and this action was in part blocked by naloxone, indicating a partial interaction with a central opioid mechanism. 99) In subsequent tests on mice, it was observed that the analgesic effect of 91 was significantly blocked by theophylline, an adenosine receptor antagonist, suggesting that the potent antinociceptive action of 91 is mainly mediated via an adenosine receptor mechanism rather than an opiate receptor mechanism. 100) Structure-activity relationship studies suggested that the cyclobutane moiety of 91 plays an important role in expression of antinociceptive action because incarvine C (92) 101) and incarvilline (93), 102) isolated from the same plant, and related compounds lacking the cyclobutane ring exhibited no or weak activity.…”
Section: )mentioning
confidence: 99%